COMPARISON OF SEVERAL PLUTONIUM GRADES RECYCLING USING MOLTEN SALT REACTOR FUJI U-1 - SUCI LESTARI (NIM : 10210019), DINI
IAEA predicted that energy generated by nuclear reactor in 2035 increased to 630 GW from 393 GW in 2009. Thus it will also increase the number of radioactive waste in the future. Nowadays, scientists are developing a new type of nuclear reactor which is Molten Salt Reactor that can recycle radioactive waste such as Plutonium. Molten Salt Reactor design can be reviewed by neutronic analysis which is effective multiplication factor, reactivity, and also fuel material composition. This research compares the effective material composition for super grade Plutonium and Uranium as fissile material. SRAC (Ver.2002) program with JENDL 3.2 library is used to help the analysis. Initial composition of Uranium fuel is 71.76% LiF, 16% BeF2, 12% ThF4 dan 0.24% 233UF4, and for Plutonium 71.76% LiF, 16% BeF2, 12% ThF4 and 0.24% *PuF4. To find the right composition that makes the reactor on critical condition for 20 years, many combination of fuel composition has been tested in this project. The diameter of the fuel duct has also been varied by fuel/graphite fraction into core 1, core 2, and core 3. Based on calculation using 233U as fissile material, fuel composition that make reactor on critical condition are: 71.76% LiF, 16% BeF2, 11.81% ThF4 and 0.43% 233UF4 (core 1), 71.76% LiF, 16% BeF2, 11.88% ThF4 and 0.36% 233UF4 (core 2) and 71.76% LiF, 16% BeF2, 11.75% ThF4 and 0.49% 233UF4 (core 3). While the fuel composition for reactor grade Plutonium that make reactor on critical condition are:71.76% LiF, 16% BeF2, 8.24% ThF4 and 4.00% *PuF4 (core 1), 71.76% LiF, 16% BeF2, 8.34% ThF4 and 3.90% *PuF4 (core 2), and 71.76% LiF, 16% BeF2, 8.30% ThF4 and 3.94% *PuF4 (core 3). Criticality achieved by Super Grade Plutonium with fuel composition: 71.76% LiF, 16% BeF2, 10.8% ThF4 and 1.44%% *PuF4 (core 1), 71.76% LiF, 16% BeF2, 11.3% ThF4 and 0.94% *PuF4 (core 2), and 71.76% LiF, 16% BeF2, 10.96% ThF4 and 1.28% *PuF4 (core 3). And criticality achieved by Weapon Grade Plutonium with composition: 71.76% LiF, 16% BeF2, 10.65% ThF4 and 1.59% *PuF4 (core 1), 71.76% LiF, 16% BeF2, 11.14% ThF4 and 1.1% *PuF4 (core 2), and 71.76% LiF, 16% BeF2, 10.44% ThF4 and 1.8% *PuF4 (core 3). Reactor needs least consentration of 233U than all three kinds of Plutonium fuel. MSR needs most consentration of Reactor Grade Plutonium among three kinds Plutonium fuel. And reacotr needs more plutonium weapon grade and least plutonium super grade.